Internal Audit Guide to the K3 Management System at Simpang Lima Gumul Hospital Kediri - Indasah; Agus Sukisno; Anggi Tiur Maduma; Sholichudin; Millania Fitri; Andre Bagaskara; Agus Heselo (Universitas STRADA Indonesia, 2024)
Hospitals in the BLUD system play an optimal role in providing health services, including the implementation of hospital operations using income sources and each part of the hospital must be able to have its own role and function but are interconnected to fully support smooth operations. The problem of a company or hospital related to occupational safety and health in general is about the readiness of management and all employees to face risks that may occur before, during and after the production process or health services with the aim of increasing effective, efficient productivity and reducing losses due to the risks incurred. Therefore, it is necessary to carry out an internal audit regarding SMK3. The main target is the management of Simpang Lima Gumul Hospital Kediri. The aim of this activity is to find out the Standard Operational Procedures for SMK3 Internal Audit at Simpang Lima Gumul Hospital Kediri. The method used in this activity is presentation regarding SMK3 Internal Audit Standard Operating Procedures to the management of Simpang Lima Gumul Kediri Hospital using power point as a medium for supplying material. The results of this activity are Standard Operational Procedures for Internal Audit of SMK3 Simpang Lima Gumul Hospital Kediri.